Da prática à reflexão: o (re)conhecimento dos limites e potencialidades da convergência das TICs aplicadas ao Coaching Universitário - Koltermann, Liana Estela Merladete de Souza Pozeczek (2017)
A new world, full of data, knowledge and excess in information, revolutionary technologies and the constant connection, have yielded to Social Communications expressive changes. And, as it cannot fail to be, the subsequent impact of the sequent media convergence was – or should be – felt, also, in educational institutions of all levels and parts in the world. In Santa Maria, RS, Brazil, it is not different, as in the case illustrated by a private institution, focused on applied social sciences, where distinct generations coexist, on and off line. But, withal, where also the traditional teaching method, that in which one speaks and all listen, depletes itself. Facing a new and urgent condition of time, institution and professors have new responsibilities, such as attending the expectations of the students in comprehending the time in which they are part of and developing solutions for discovering, perfecting and potentiating their new competences and abilities. While the physical space of class and the stopwatch resignify themselves, new alternatives, generally extracurricular ones, are searched for, such as the university level coaching. Facing the enhancement of an initiative in the area and in the aforementioned institution, a question is put forward: in this context, what are the limits and potentialities of information and communication technologies applied to an extracurricular project of university level coaching? Clarifying and challenging this guiding question, this paper passes through a dynamic of investigation in a procedure of Case Study, based in techniques of interview applications and participant’s observation. It happens, first, through higher education in Brazil, history, scenery and tendencies; consequent effects of convergence of Information and Communication Technologies and; through conceptual and practical (re)admission of mentoring, coaching and counseling terms, besides their singularities and similarities in the process of communication and institutional interaction. It presents, yet, the archetype of a virtual ambience of teaching and exchange of experiences aiming the extension of the project in sight and, especially, contributing for the research field in the area of Educational Technologies network. In the digressions, it emphasizes technical and structural conditions as a limiting factor and; points out tool and methodology as potential corresponding to the continuous demand for innovation, legitimizing the multidisciplinary status of guided actions to the development and management of knowledge.